Self-deception in financial decisions - Maciejasz-Świątkiewicz, Marta; Musiał, Mateusz (Samooszukiwanie w decyzjach finansowych, 2019)
Self-deception is classified as the one of the decision-making errors which impede making reasonable decisions. The efficiency of the financial market is associated with the belief that all the participants of the market behave reasonably. They maximise their utility and are able to process all incoming information in the correct way. Considering the fact that financial market anomalies happen, it should be considered that the efficiency of this market is a specific situation in which it may be found. In this work, the research results of the conducted experiment were described. The hypothesis was studied that persons of a higher financial status are more likely to undertake more risky financial decisions which may result in obtaining higher collected financial funds. As a result of the conducted experiment the working hypothesis was confirmed. Due to self-deception consisting in strong identification with the chosen status in the game, strengthened with their own convictions regarding the behaviour of particular professional group representatives, persons with a higher status showed a much greater tendency to risk than persons with a lower status
Financial Sciences. Nauki o Finansach, 2019, vol. 24, no. 3, s. 23-34
Keywords: self-deception; financial decisions; behavioural finance; samooszukiwanie; decyzje finansowe; finanse behawioralne